Workplace grapevine its impact on work relations and performace - Asuncion, Ronahlee A. (2010)
This article explores the dynamics of workplace grapevine as performed and practiced by the administrative personnel of the University of the Philippines Diliman. The findings reveal that grapevine is a powerful channel of informal communication used to perpetuate organizational values, exert power, control and influence in the workplace. Relationships either flourish or weaken which inevitably affect work relations and performance. Indeed grapevine is a natural phenomenon in organizations with far and wide ranging effects to both the workers and the workplace. To obtain valid and reliable information, a triangulation of data source and research method was done. Focus group discussions, key informant interviews, and diaries of administrative personnel from various units of the University were utilized.
Keywords: Communication; Interpersonal relations; University of the Philippines (Diliman)